The Stackelberg Model in Territorial Planning - Lavlinskii, S. M.; Panin, A. A.; Plyasunov, A. V. (Automation and remote control, 2019)
We propose a new model for the formation of a public-private partnership mechanism, formulated as a bilevel Boolean programming problem. We show that this task is ∑ 2 P -hard in both optimistic and pessimistic forms. We develop a stochastic iterative algorithm for solving this problem. We also present computational experiments on real information that demonstrate the capabilities of the proposed approach.